2015
DOI: 10.1016/j.cancergen.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A and TERT promoter mutations in dedifferentiated meningioma

Abstract: While WHO grade I meningiomas are considered benign, patients with WHO grade III meningiomas have very high mortality. The principles underlying tumor progression in meningioma are largely unknown yet a detailed understanding of these mechanisms will be required for effective management of patients with these high-grade, lethal tumors. We present a case of an intraventricular meningioma that at first presentation displayed remarkable morphologic heterogeneity – comprised of distinct regions independently fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 31 publications
2
63
0
1
Order By: Relevance
“…We also sequenced selected genes in 76 additional high-grade meningiomas for a total of 134 high-grade meningiomas (Supplementary Table 1 & Supplementary Figure 1). We compared the data derived from these 134 samples to previously published data from 595 sporadic meningiomas profiled with whole genome or whole exome sequencing (108 low-grade and 22 high-grade tumors tumors), and targeted capture sequencing (348 low-grade and 117 high-grade tumors) [6, 7, 912]. We used these data to characterize somatic mutations (including insertions and deletions), somatic copy-number alterations (SCNAs), and rearrangements genome-wide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also sequenced selected genes in 76 additional high-grade meningiomas for a total of 134 high-grade meningiomas (Supplementary Table 1 & Supplementary Figure 1). We compared the data derived from these 134 samples to previously published data from 595 sporadic meningiomas profiled with whole genome or whole exome sequencing (108 low-grade and 22 high-grade tumors tumors), and targeted capture sequencing (348 low-grade and 117 high-grade tumors) [6, 7, 912]. We used these data to characterize somatic mutations (including insertions and deletions), somatic copy-number alterations (SCNAs), and rearrangements genome-wide.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this possibility, we sequenced these genes, which are the four most common non- NF2 driver alterations, in our extension cohort of 76 samples. We then integrated the data with previously published sequencing data from 595 additional meningiomas [6, 7, 9, 10, 12]. For each gene, we compared rates of mutation among both high- and low-grade meningiomas (Figure 1D) [6, 7].…”
Section: Resultsmentioning
confidence: 99%
“…Antigen retrieval was with a pressure cooker. Staining was attempted with anti-HFH4 antibody [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (ab40869; Abcam, Cambridge, MA, USA) but despite recognizing FOXJ1 in ciliated Fallopian tube cells, staining was not obtained in ependymoma tumour cells. Negative control staining was performed using normal/non-immune rabbit serum, immunoglobulin fraction (X0936; DakoCytomation Corp, Carpinteria, CA, USA).…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
“…epigenetic subgroups in medulloblastoma [8][9][10] and ependymoma 11 , or isocitrate dehydrogenase (IDH) status in diffuse glioma [12][13][14] . Recent studies identified telomerase reverse transcriptase (TERT) promoter mutations in a small subset of meningiomas to be associated with higher risk of recurrence and shorter time to progression 15,16 , and four large exome-sequencing efforts focusing on WHO grade I meningiomas have identified recurrently mutated genes beyond the long-known association with NF2 [17][18][19][20] . Yet, these findings only cover only a fraction of meningiomas and have not all been adequatelythoroughly tested for their prognostic relevance.…”
Section: Introductionmentioning
confidence: 99%